Bandas de música e Políticas Públicas: um estudo sobre práticas educativas nas bandas do Ceará - França, Antonio Arley Leitão (2017)
The present research aimed to understand the interrelationships between the State System of Wind Bands of Ceará - SEBAM/CE, the state´s wind bands and their musical educational practices, being three bands located in the metropolitan region of Fortaleza were the bands chosen for the study. The qualitative research used as a methodological approach the case study, more precisely the study of multiple cases. The methodological procedures used to obtain the data in the research were semi-structured interviews and observations of classes and rehearsals. The analysis of the data showed that if on the one hand SEBAM/CE was influenced by the demands of the wind bands themselves, on the other hand the wind bands of Ceará changed the course of their history under the influence of the practices proposed by SEBAM/CE. The study revealed that SEBAM/CE brought new knowledge to musicians and band directors, influencing the reformulation of traditional practices, proposing new aesthetics and fostering the survival of the Ceará State wind bands.